Challenges and Prospects for Organic Farming: A Case Study from India - Kaur, Harmandeep (Gyan Management Journal, 2023)
Several past studies have considered organic farming as it serves as a responsive sustainable approach to the rural development. This study emphasises and focuses on the opportunities and constraints in organic farming in context of India. There are several cost and marketing related problems specific to organic food. This study identify the following areas to addresss these problems in the country: develop a regional programme to address specific regional problems, take into account the unique conditions prevailing in the region; provide financial assistance for the effective implementation of organic projects and programmes, access to advanced technology, effective information sharing platforms. The organic movement’s capacity for adaptation and learning from past experiences will determine if organic farming is able to fully realise its capacity for fostering resilience( Milestad and Darnhofer, 2003).